ANALISIS PROGRAM 5S (SENYUM, SALAM, SAPA, SOPAN, SANTUN) DALAM MEMBENTUK KARAKTER EMPATI SISWA KELAS IV SD NEGERI SUKARESMI - Gumilang, Yayang; Mas Ramadhan, Gilang; Ma'arif, Syamsul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Empathy is one of the essential character values that should be developed from the elementary school level, as it enables students to understand, appreciate, and respond positively to the feelings and needs of others. However, some students still demonstrate low levels of empathy, including limited concern for peers, inadequate cooperation, and low sensitivity toward others' difficulties. This study aimed to analyze the development of students' empathetic character through the implementation of the 5S Program (Smile, Greeting, Courtesy, and Politeness) among fourth-grade students at SD Negeri Sukaresmi. This research employed a qualitative approach using a case study design. Data were collected through observations, interviews, and documentation involving the principal, the fourth-grade teacher, and fourth-grade students as research participants. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while data trustworthiness was established through source and technique triangulation. The findings revealed that the implementation of the 5S Program contributed to the development of students' empathetic character through the enhancement of cognitive aspects, reflected in students' ability to understand others' perspectives; affective aspects, reflected in caring attitudes and emotional sensitivity toward peers; and motoric aspects, reflected in helping behaviors, respect, cooperation, and polite social interactions. The development of empathetic character was supported by teachers' role modeling, school culture, and parental involvement, while differences in students' individual characteristics and external environmental influences became the main challenges in strengthening empathy.